Evaluation of the soft tissue components of the equine stifle using 3 Tesla magnetic resonance imaging under flexion, extension, and loading - Stedman, Jocelyn Marie (Kansas State University, 2024)
High field magnetic resonance imaging (MRI) of the equine stifle provides high resolution information about soft tissues that is useful in the diagnosis of stifle lameness. The aim of this prospective anatomic study was to describe the appearance, position, size, and shape of the equine femorotibial ligaments, meniscal ligaments, and menisci using 3 T MRI under extended, extended loaded, and flexed conditions. Additionally, histologic examination of the collateral and cruciate ligaments of a single stifle was performed to compare with MRI images. In extension, mild variations in MRI signal intensity were apparent in the cruciate ligaments and the cranial had two distinct longitudinal regions indicating two ligament bundles. Flexion had minor effects on cruciate ligament signal intensity and altered the tibial angles of attachment. Histology indicated that both cruciate ligaments were comprised of two fiber bundles. The collateral ligaments were the same low-signal intensity. The medial collateral ligament had a smaller cross-sectional area than the lateral, and flexion increased the length of the medial collateral ligament and the cross-sectional area of the lateral. Low loads in extension did not affect the MRI appearance of stifle soft tissues. Flexion of the stifle impacted cruciate ligament insertion angles and the size and shape of the collateral ligaments. This study provides support for the use of MRI to understand the anatomy and function of stifle ligaments.
Keywords: Stifle; Horse; Cruciate ligaments; Magnetic resonance imaging